1999
DOI: 10.1080/09595239996590
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs of doctors prescribing methadone to addicts in the Westfalen‐Lippe region of Germany

Abstract: Doctors who prescribe methadone to heroin addicts in the Westfalen-Lippe region of Germany were surveyed in 1996 to develop and use German versions of existing Australian and American scales. Two scales were developed from 247 responses using confirmatory factor analysis and Cronbach˜s alpha. The 10-item abstinence orientation (AO) scale measures strength of commitment to abstinence-orientated treatment policies, and the five-item disapproval of drug use (DDU) scale measures disapproval of illicit drug use. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
1
2
0
2
Order By: Relevance
“…The instrument was developed in NSW, Australia, in 1996 [ 7 ]. The instrument had been used in several other studies in Australia [ 8 - 11 ], USA [ 12 - 15 ], Netherlands [ 16 ], Germany [ 17 ], and Spain [ 18 ]. Items tailored towards the country's OMT system were added when the instrument was used outside of Australia [ 12 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was developed in NSW, Australia, in 1996 [ 7 ]. The instrument had been used in several other studies in Australia [ 8 - 11 ], USA [ 12 - 15 ], Netherlands [ 16 ], Germany [ 17 ], and Spain [ 18 ]. Items tailored towards the country's OMT system were added when the instrument was used outside of Australia [ 12 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This barrier was evidenced in Article I, where the setting (Gävleborg) which reported more access to abstinence-oriented treatment services also had lower acceptance for the harm reduction philosophy, as well as less willingness to implement certain harm reduction services. This pattern aligns with other research, which indicates that care providers with an abstinence orientation are less inclined to recommend or provide harm reduction services such as OST, NSP, and overdose prevention (Brown, 2022;Gerlach & Caplehorn, 1999;.…”
Section: Shaping the Care That Providers Can Offer And How Clients Re...supporting
confidence: 88%
“…A review by Brown (2022) found that education on OST, exposure to OST in clinical settings, and a clinical treatment orientation were the most important factors enhancing willingness to provide OST. A variety of studies have demonstrated that, for instance, lower knowledge about the evidence of methadone as a treatment option is correlated to stronger support for abstinence-oriented policies (Aletraris et al, 2016;Gerlach & Caplehorn, 1999;Russell et al, 2011). Similarly, found that substance use professionals who reported prioritizing abstinence, and who reported lack of knowledge of certain interventions, were less supportive of harm reduction measures such as NSP, OST, and overdose prevention sites.…”
Section: Service Provider Attitudes and Care Experiencesmentioning
confidence: 99%
“…Knapp 57% der Opioidabhängigen befinden sich in einer Substitutionsbehandlung. Gegenüber der Opioidsubstitution bei Inhaftierten war lange Jahre international und auch in Deutschland eine deutliche Skepsis zu beobachten 2 . In den letzten Jahren hat, auch durch das EGMR-Urteil vom 01.09.2016 3 , ein Einstellungswandel begonnen, das Thema Sucht und Haft erfährt zunehmende wissenschaftliche und öffentliche Aufmerksamkeit und die Substitutionsquoten steigen langsam an.…”
Section: Introductionunclassified
“…Die regional unterschiedliche, teils schleppende Etablierung der Substitution in Haft ist einerseits strukturell begründet, beispielsweise durch Unterschiede in der Personalausstattung, der Gefangenenpopulation und der externen Versorgungsstruktur 4 6 7 . Aber auch das Wissen und die Einstellungen des behandelnden Personals beeinflussen die Indikationsstellung maßgeblich 2 4 8 9 10 . Kouyoumdjian et al 9 befragten 27 kanadische Haftärztinnen und -ärzte zur Behandlungspraxis bei opioidabhängigen Inhaftierten.…”
Section: Introductionunclassified